2016
DOI: 10.5301/ejo.5000813
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Phacoemulsification Cataract Surgery with Low versus Standard Fluidic Settings and the Impact on Postoperative Parameters

Abstract: Although the surgical time and ECD were significantly higher in the group with low fluidic settings, there were no differences in the CCT, ECD, macular thickness, or inflammation postoperatively between the low and standard fluidic settings during phacoemulsification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Keeping aside machine and tip factors, several other factors can lead to ECL during PKE, as observed by different authors, such as incision size and design, increasing hardness of nucleus, different PKE techniques, differing composition of irrigating fluids or OVD /drugs, instrumental injury, surgeons’ experience, older age, type, and delivery technique of IOL, formation of free radicals, smaller pupil size. [ 18 19 20 ] In our study, other than modes, we tried our best to avoid the bias arising from all these factors as described in methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Keeping aside machine and tip factors, several other factors can lead to ECL during PKE, as observed by different authors, such as incision size and design, increasing hardness of nucleus, different PKE techniques, differing composition of irrigating fluids or OVD /drugs, instrumental injury, surgeons’ experience, older age, type, and delivery technique of IOL, formation of free radicals, smaller pupil size. [ 18 19 20 ] In our study, other than modes, we tried our best to avoid the bias arising from all these factors as described in methodology.…”
Section: Discussionmentioning
confidence: 99%
“…The study selection flowchart is presented in Supplementary Figure S1. We initially identified a total of 1,111 records through the systematic search, and after screening the study titles and abstracts, 12 potential articles (4,(9)(10)(11)(12)(13)(20)(21)(22)(23)(24)(25) were evaluated for final eligibility. Of these potential records, we excluded two studies which were not designed as randomized controlled trials (23,24), one study lacking comparisons between high-flow and low-flow phacoemulsification cataract surgery (25), and three studies without final reports (20)(21)(22).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…In addition, phacoemulsification may also trigger inflammation, thus leading to macular edema. However, several randomized controlled trials (RCTs) with small sample sizes reported inconsistent surgical outcomes, regarding ECL, central corneal thickness (CCT) and central macular thickness (CMT), after high-or low-flow phacoemulsification cataract surgery (4,(9)(10)(11)(12)(13). To summarize the current evidence and better inform clinical decision-making, we conducted a systematic review and meta-analysis study on the surgical outcomes reported from RCTs comparing high-flow and low-flow phacoemulsification cataract surgery.…”
Section: Introductionmentioning
confidence: 99%
“…A certain amount of fluid passes through the zonules from the anterior chamber to the vitreous cavity, inducing anatomical and biochemical changes, increasing the risk of PVD . In particular, the phacoemulsification technique and the level of experience of the surgeon can additionally increase the amount of intraoperative manipulation and prolong surgery time . Longer surgery and operative settings with more fluid movement and turbulence imply that an additional amount of vibrations might be transferred to the anterior hyaloid, which induces PVD …”
mentioning
confidence: 99%